М.И. Гладких и социоисторическое направление в палеолитоведении - Палиенко, С.В. (Археологія і давня історія України, 2011)
В статье рассматривается развитие социоисторического направления в советском палеолитоведении. Анализируется теоретическое наследие
М.И. Гладких в рамках научной школы П.П. Ефименко. У статті розглядається розвиток соціоісторічного
напрямку в радянському палеолітознавстві. Аналізується теоретична спадщина М.І. Гладких в рамках наукової школи П.П. Єфименка. The P.P. Efimenko’s Kyiv scientific school was formed
during the second half of the 20th century. The sociohistorical
approach was realized in the Paleolithic archaeology by
P.P. Efimenko and his disciples. One of them was A.N. Rogachev
formulated the fundamental historical approach
demanding to study the historical process in its spatial
and chronological limits. Another P.P. Efimenko’s disciple
was I.G. Shovkoplias realized the fundamental historical
approach in practice in Ukraine during the 1960s years.
His follower was M.I. Gladkyh continued to develop his
master’s ideas. Main results of his work were stated in the
doctoral thesis named «The historical interpretation of the
Upper Paleolithic (by the materials from the territory of
Ukraine)». There is the application in practice of the sociohistorical
approach was formulated in theoretical contributions
of V.F Gening. The returning to the scientific heritage
of M.I. Gladkyh can help to find the solution of actual
problems of the contemporary Paleolithic archaeology.